The fierceness of fronted /s/: Linguistic rhematization through visual transformation - Calder, Jeremy (Language in Society, 2019)
This article explores the roles that language and the body play in the iconization of cross-modal personae (see Agha 2003, 2004). Focusing on a community of radical drag queens in San Francisco, I analyze the interplay of visual presentation and acoustic dimensions of /s/ in the construction of the fierce queen persona, which embodies an extreme, larger-than-life, and anti-normative type of femininity. Taking data from transformations—conversations during which queens visually transform from male-presenting into their feminine drag personae—I explore the effect of fluid visual presentation on linguistic production, and argue that changes in both the linguistic and visual streams increasingly invoke qualia (see Gal 2013; Harkness 2015) projecting ‘harshness’ and ‘sharpness’ in the construction of fierce femininity. I argue that personae like the fierce queen become iconized through rhematization (see Gal 2013), a process in which qualic congruences are construed and constructed across multiple semiotic modalities. (Iconization, rhematization, qualia, sociophonetics, gender, personae, drag queens)*
Disponible en ligne https://www-cambridge-org.proxy.bibliotheques.uqam.ca/core/journals/language-in-society/article/fierceness-of-fronted-s-linguistic-rhematization-through-visual-transformation/ADD4290AEAAA81B3474898265590BDD6
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; drag queen; identités LGBTQIA2+; lin2685; linguistique; premier cycle; queer; ressource en ligne; régions géographiques; san francisco; sciences humaines; thématiques; états-unis

Góor-jigéen: la resignification négative d’une catégorie entre genre et sexualité (Sénégal) - Christophe Broqua (Socio, 2019)
Dans de nombreux pays africains, il a existé et il existe encore parfois des figures institutionnalisées de la diversité de genre. C’est le cas, au Sénégal, du góor-jigéen, littéralement « homme-femme » en langue wolof. Évoquée dans certains récits d’observateurs dès le xixe siècle, cette figure a rarement été décrite ou analysée avec précision dans la littérature savante. Pendant longtemps, le góor-jigéen était un homme biologique présentant des attributs féminins et occupant préférentiellement certaines fonctions sociales. Son statut et sa place étaient reconnus au sein de la société sénégalaise. Progressivement, l’expression est devenue synonyme d’homosexuel masculin et elle est aujourd’hui le plus souvent utilisée comme une injure. Elle a donc connu une « resignification négative », traduisant la transformation d’une catégorie de genre en une catégorie d’orientation sexuelle. Cet article retrace l’histoire de la figure du góor-jigéen et analyse les conditions qui ont rendu possible la transformation de sa signification et de sa position sociales.
Disponible en ligne à https://journals-openedition-org.proxy.bibliotheques.uqam.ca/socio/3063
Keywords: LGBTQIA2+; afrique; approches et analyses; cours; discipline; identités LGBTQIA2+; lin2685; linguistique; premier cycle; queer; ressource en ligne; régions géographiques; sciences humaines; sénégal; thématiques

The Oxford handbook of language and sexuality - Hall, Kira; Barrett, Rusty (Oxford University Press, 2018)
Disponible en ligne à https://academic.oup.com/edited-volume/42645?login=true Donné en lecture au cours LIN2685, King, Brian W. "Language and embodied sexuality", pp1-20.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; outils; ouvrages de références; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; sociolinguistique; thématiques

Language and masculinities: performances, intersections, dislocations - Milan, Tommaso M. (Routledge, 2015)
This volume showcases cutting-edge research in the linguistic and discursive study of masculinities, comprising the first significant edited collection on language and masculinities since Johnson and Meinhof’s 1997 volume. Overall, the chapters are linked together by a critical analytical perspective that seeks to understand the relationships between discourse, masculinities, and power. Whereas some of the chapters offer detailed, linguistically informed critiques of the ways in which old and new expressions of masculinities are complicit in the reproduction of men’s hegemonic positions of power, others provide a more complex picture, one in which collusion and subversion go hand in hand. Contributions argue for the need for research on language and masculinities to expand its remit so as to engage with "gay masculinities," and unsettle gendered categories in order to consider the ways in which women, transgender, and intersex individuals also perform a variety of masculinities. Finally, unlike Johnson and Meinhof’s 1997 collection, this volume not only offers a wider—and perhaps "queerer" perspective—on the study of language and masculinities, but also covers a broader geographical and socio-cultural spectrum, including work on Brazil, Israel, New Zealand, Singapore, and South Africa.
Donné en lecture au cours LIN2685, Jones, Lucy. Masculinity in Lesbian Discourse, the Case of 'Butch' vs 'Femme', p 174-196.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; masculinité; premier cycle; queer; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociolinguistique; sofia; thématiques; études de genres

Queer excursions: retheorizing binaries in language, gender, and sexuality - Zimman, Lal; Davis, Jenny L.; Raclaw, Joshua (Oxford University Press, 2014)
Across scholarship on gender and sexuality, binaries like female versus male and gay versus straight have been problematized as symbols of the stigmatization and erasure of non-normative subjects and practices. The chapters of Queer Excursions offer a series of distinct perspectives on these binaries as well as on a number of other, less immediately apparent dichotomies that nevertheless permeate the gendered and sexual lives of speakers in various contexts. Some chapters focus on the limiting or misleading qualities of binaristic analyses, while others suggest that binaries are a crucial component of social meaning within particular communities of study. Rather than simply accepting binary structures as inevitable, or discarding them from our analyses entirely based on their oppressive or reductionary qualities, this volume advocates for a retheorization of the binary that affords more complex and contextually grounded engagement with speakers’ own orientations to dichotomous systems. It is from this perspective that contributors identify a number of diverging conceptualizations of binaries—including those that are non-mutually exclusive, those that liberate in the same moment that they constrain, those that are imposed implicitly by researchers, and those that recontextualize familiar divisions with innovative meanings. With each chapter having a perspective on locally salient linguistic practices that help constitute gender and sexuality in marginalized communities, what the contributions to Queer Excursions together demonstrate is that researchers must be careful to avoid the assumption that our own preconceptions about binary social structures will be shared by the communities we study.
Donné en lecture au cours LIN2685 et POL4105, Jenny L. Davis, “More Than Just ‘Gay Indians’”: Intersecting Articulations of Two-Spirit Gender, Sexuality, and Indigenousness, pp62-80.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; pol4105; premier cycle; queer; ressource en ligne; sciences humaines; sociolinguistique; sofia; thématiques

Langage, genre et sexualité - Auger, Nathalie (Éditions Nota Bene, 2011)
L'objectif de cet ouvrage est d'examiner les liens complexes entre langage, genre et sexualité. En adoptant un positionnement résolument critique, qui met l'accent sur les aspects historique, politique et social des pratiques langagières, cet ouvrage part de l'idée que le genre et l'identité sexuelle sont avant tout des constructions sociales et idéologiques qui trouvent une forme de matérialité, entre autres, dans les discours et les pratiques sociales. Nous croyons que ces processus langagiers participent à la formation des différences et des inégalités - sans toutefois en être l'unique cause -, qu'ils contribuent à la réification des catégories au même titre qu'ils permettent d'en créer de nouvelles.–Résumé de l'éditeur.
Section: 293 pages : illustrations (certaines en couleur), tableaux; 23 cm.
Keywords: LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; europe; france; francophonie; féminisme matérialiste; identités LGBTQIA2+; langue; lin2685; linguistique; premier cycle; queer; québec; régions géographiques; sciences humaines; sexualité; sociolinguistique; thématiques